2009
DOI: 10.5194/acpd-9-5679-2009
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A consistent molecular hydrogen isotope chemistry scheme based on an independent bond approximation

Abstract: Abstract. The isotopic composition of molecular hydrogen (H2) produced by photochemical oxidation of methane (CH4) and Volatile Organic Compounds (VOCs) is a key quantity in the global isotope budget of (H2). The many individual reaction steps involved complicate its investigation. Here we present a simplified structure-activity approach to assign isotope effects to the individual elementary reaction steps in the oxidation sequence of CH4 and some other VOCs. The approach builds on and extends the work by Gers… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…The two‐way nested setup of the TM5 model [ Krol and Houweling , ] was recently enhanced by implementing a H 2 isotope chemistry scheme [ Pieterse and Krol , ], an H 2 emission inventory adopted from the project for Global and regional Earth system Monitoring using Satellite and in situ data [GEMS: Schultz and Stein , ], a soil moisture dependent deposition parametrization [ Sanderson and Collins , ], and a stratospheric parametrization for H 2 and HD [ Rahn and Eiler , ; McCarthy and Boering , ; Pieterse and Krol , ]. Our previous study [ Pieterse and Krol , ] was primarily focussed on the introduction and global evaluation of the new H 2 isotope chemistry scheme.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The two‐way nested setup of the TM5 model [ Krol and Houweling , ] was recently enhanced by implementing a H 2 isotope chemistry scheme [ Pieterse and Krol , ], an H 2 emission inventory adopted from the project for Global and regional Earth system Monitoring using Satellite and in situ data [GEMS: Schultz and Stein , ], a soil moisture dependent deposition parametrization [ Sanderson and Collins , ], and a stratospheric parametrization for H 2 and HD [ Rahn and Eiler , ; McCarthy and Boering , ; Pieterse and Krol , ]. Our previous study [ Pieterse and Krol , ] was primarily focussed on the introduction and global evaluation of the new H 2 isotope chemistry scheme.…”
Section: Methodsmentioning
confidence: 99%
“…The resulting framework was also used to evaluate the stable H 2 isotope budgets previously reported by Gerst and Quay [], Rahn and Kitchen [], Rahn and Eiler [], and Rhee and Brenninkmeijer []. A full H 2 isotope chemistry scheme was recently implemented in the TM5 model [ Pieterse et al ., , ] and used to further constrain the global budget of H 2 with δ [ D H 2 ] measurements. Both studies showed that the modeled tropospheric δ [ D H 2 ] is very sensitive to the values of the isotopic composition of stratospheric molecular hydrogen that is heavily enriched in deuterium [ Rahn and Eiler , ; Röckmann and Rhee , ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it became possible to analyze the D content of H 2 (δD) in small atmospheric samples at natural isotopic abundances . These measurements enabled the study of different components of the H 2 cycle and helped constrain the atmospheric H 2 budget, which as a consequence is currently relatively well understood on the large scale . Although H 2 isotope measurements have proven useful, they are difficult to perform, and only few labs had or have this capability.…”
Section: Background and Introductionmentioning
confidence: 99%